IMPACT OF THE GOVERNMENT DEBT ON ECONOMIC DEVELOPMENT OF COUNTRY - MARSHALOK, Taras; MOROZ, Ivanna (Scientific journal «World of Finance», 2019)
Introduction. An increase in public debt may have a negative, neutral or positive impact on the country's economic development. A big loan does not mean big growth; it all depends on how the public money is spent. The same amount of money spent by governments from different countries has a different meaning for domestic development and the dynamics of public debt. The reasons are differences in the size of GDP, the structure of government borrowings, the shadow economy.Purpose. The objective of this paper is to deepen the theoretical backgrounds and applied aspects of influence of the public debt on the economic development of the country.Methods. In the research process, a set of research methods and approaches were used: systemic, structural-functional, comparisons and others.Results. The problem of a high level of public debt is acute in many countries throughout the world, including Ukraine. Nobody can say for sure whether a high public debt holds back the country's economic development. Theoretically, economically weaker countries, having regard to the financial constraints and economic needs, should have a higher level of public debt in relation to GDP than countries with high levels of development. However, comparing the data on the ratio of public debt and GDP in the EU, it can be noted the following: the higher indicators in the more developed countries of the EU. The latter, in fact, are the largest lenders of the world economy and at the same time have the largest volumes of the public debt both in absolute terms and in relation to GDP.As a result of the unsatisfactory financial state of the public sector, household saving goes to the repayment of the higher-level commitments, and not for the financing of the development of companies. This is especially problematic if we look at the situation of future generations – they will have less capital at their disposal. Public debt is a reduction in future revenues; hence, it is an intergenerational problem.Conclusions. It is possible to make proposals that will have a significant impact on the growth of the economy and the reduction of the public debt:– internal borrowing but not the external loans are economically justified. In this case, the debts do not increase the money base and the turnover of funds is carried out within the state;– entrepreneurship requires the systematic and consistent support that will stimulate the economic development, which needs stable business conditions in the long run.